UJI DAYA HAMBAT EKSTRAK ETIL ASETAT DAUN BINAHONG (Anredera coliforlia (Ten.) Steenis) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus DAN Escherichia coli. - Wahyuddin JUmardin; Masnawati Masnawati (As-Syifaa Jurnal Farmasi, 2015)
Binahong (Anredera coliforlia (Ten.) Steenis) is a potential medicinal plants that can superintend with different kinds of diseases. Research on antibacterial activity of binahong leaves and the secondary metabolites content ever done that in binahong leaves contained alkaloids, saponins, polyphenols. This research is a laboratory experiments that aim to find out the inhibition of leaves binahong ethyl acetate extract (Anredera coliforlia (Ten.) Steenis) against bacteria test. Binahong leaf extract work done by maceration method. Bacteria test i.e. Staphylococcus aureus and Escherichia coli. The zone of inhibition are determined for concentration ranging between 5%, 10%, 15%, and 20%. Test of antibacterial activity is done using paper discs and disc diffusion method. The results of research can be drawn the conclusion that the ethyl acetate extract, binahong leaves at concentrations of 5% inhibition zone not seen against the bacteria Staphylococcus aureus, Escherchia coli and bacteria while at concentrations of 10%, 15% and 20% visible inhibition zone against both the bacteria i.e. 1.7 mm, 2.0 mm and 2.6 mm for the bacteria Staphylococcus aureus and 1.8 mm and 2.3 mm 2.8 mm for the bacterium Escherichia coli. It can be said that the extract of binahong leaves influential ethyl acetate can potentially inhibit the growth of Staphylococcus aureus and Escherichia coli, and based on the diameter of the inhibition zone caused by any concentration of the extract can also be inferred that the higher the concentration of a sample is then the higher the diameter of the inhibition zone is generated.